CULTURAL COMMUNICATION’S ROLE IN K-POP PROGRESS AND ITS IMPACT ON YOUNG GENERATION IN THE SOCIAL MEDIA ERA - Selamat Riadi (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2025)
Imperialism does not only take the form of military power by a strong country, but can also be through cultural domination. Through new media technologies like fan blogs, peer-to-peer sites, video sharing sites, microblogging, and mobile internet, the Korean wave spread K-pop (Korean popular music). The point of this exploration is to make sense of the impact of virtual entertainment on K-pop fan culture, beginning with explanations about the most recent improvements in the more youthful age's cooperation in web-based entertainment, collaborations with transcultural famous substance streams, and the positive and adverse consequences on K-pop fans. Qualitative studies using relevant keywords, such as cultural imperialism, K-pop, social media, and transcultural, were used in electronic article search methods. From the search results, it can be concluded that Kpop culture has succeeded in occupying the world because of the Korean entertainment agency's social media strategy. Arrangement of key plans of action with virtual entertainment, expanding different web-based entertainment channels, drawing in clients with on the web and disconnected advancements, and animating crowds with elite substance has made Kpop famous with different gatherings. Indonesian culture and Kpop can go hand in hand and even make teenagers more creative in developing themselves, but they must be accompanied by their parents.